Robust Synchronization of Fractional-Order Chaotic System Subject to Disturbances - Dongya Li; Xiaoping Zhang; Shuang Wang; Fengxiang You (Mathematics, 2022)
This paper studies the synchronization problem for a class of chaotic systems subject to disturbances. The nonlinear functions contained in the master and slave systems are assumed to be incremental quadratic constraints. Under some assumptions, a feedback law is designed so that the error system behaves like the <semantics>H∞</semantics> performance. Meanwhile, the detailed algorithm for computing the incremental multiplier matrix is also given. Finally, one numerical example and one practical example are simulated to show the effectiveness of the designed method.